Challenges and strategies in meeting urban tree canopy targets: A scenario discovery analysis to guide urban forest planning in new developments - Raymundo Marcos Martinez; Natthanij Soonsawad; Mariana Dias Baptista; Stephen Cook; Guy Barnett; Joseph Chee; Tim Field; Tim Muster (Trees, Forests and People)
With increasing urban populations worldwide, new developments face ambitious tree canopy cover targets to mitigate urban heat, reduce stormwater runoff, support biodiversity, and promote health benefits. Achieving substantial tree canopy cover in dense urban areas is challenging due to space constraints and varying species performance. This study explores strategies for achieving a 40 % tree canopy cover target in a new development within the Western Sydney Aerotropolis Precinct, NSW, Australia, using scenario discovery analysis. We identified 54 climate-adapted tree species and analysed 1,372 scenarios considering tree spacing, mortality rates, and open space tree cover requirements. Using i-Tree Eco, we projected annual tree canopy growth over a 50-year period across seven urban typologies. Our results indicate that achieving the 40 % target is feasible only with a diverse mix of Australian native, indigenous, and exotic species and that tree mortality significantly impacts long-term canopy growth. While higher canopy cover in open spaces and effective species selection are crucial, the 40 % target remains difficult to achieve under most scenarios. Strategies to reduce net tree losses, optimise tree spacing, and implement effective landscape design are essential for substantial canopy cover. This research highlights the importance of promoting tree cover growth on private land and provides best practices for urban tree design, establishment, and management, offering insights transferable to other cities globally.